Consistency of a numerical approximation to the first principal component projection pursuit estimator - Bali, Juan Lucas (2014)
We generalize to functional data, the approach given by Croux and Ruiz-Gazen (1996) to compute robust projection-pursuit principal direction estimators, allowing also for smoothness in the estimators. Consistency of the approximated first principal direction estimator is derived.